Isopropyl Myristate Continuous Synthesis In A Packed-Bed Reactor Using Lipase Immobilized On Magnetic Polymer Matrix - Silva, Mateus V. C.; Souza, Caio A. P. De; Oliveira, Pedro C. De; Heizir F. De Castro; Freitas, Larissa (Zenodo, 2018)
Abstract — The aim of this study was to synthesize isopropyl myristate, an emollient ester, in a continuous-flow packed-bed reactor using Candida antarctica lipase immobilized on poly(styrene-co-divinylbenzene) matrix prepared by suspension polymerization and magnetized by co-precipitation of Fe 2+ and Fe 3+ in alkaline medium. To determine the best esterification conditions, we investigated the effects of acid/alcohol molar ratio (1:5, 1:10, and 1:15) on reaction yield in shake flasks. The three tested conditions provided similar results, esterification yields of approximately 80%. An acid/alcohol molar ratio of 1:15 was chosen for further experiments because it allowed for better operability of the bioreactor. Subsequently, we compared the reactor performance in up flow and down flow modes. This experiment showed that greater ease of operation was achieved with down flow operation. We also evaluated the influence of space time (8 and 20 h) on reaction yield and productivity. A space time of 8 h provided better results. An experimental system consisting of two bioreactors and a molecular sieve packed column was used to remove the water formed during esterification and thus increase the yield of isopropyl myristate. There was a significant improvement in performance with the use of the two-stage system, which resulted in almost complete conversion of reagents, an increase of about 150% in biocatalyst half-life, and an isopropyl myristate productivity of 25 g L −1 h −1 , confirming the beneficial effect of adding a water extraction column to the experimental system.